Using ecosystem integrity to maximize climate mitigation and minimize risk in international forest policy - Rogers, Brendan M.; Mackey, Brendan; Shestakova, Tatiana A.; Keith, Heather; Young, Virginia; Kormos, Cyril F.; DellaSala, Dominick A.; Dean, Jacqueline; Birdsey, Richard; Bush, Glenn; Houghton, Richard A.; Moomaw, William R. (Frontiers in Forests and Global Change, 2022)
Several key international policy frameworks involve forests, including the Paris Agreement on Climate Change and the Convention on Biological Diversity. However, rules and guidelines that treat forest types equally regardless of their ecosystem integrity and risk profiles in terms of forest and carbon loss limit policy effectiveness and can facilitate forest degradation. Here we assess the potential for using a framework of ecosystem integrity to guide policy goals. We review the theory and present a conceptual framework, compare elements of integrity between primary and human-modified forests, and discuss the policy and management implications. We find that primary forests consistently have higher levels of ecosystem integrity and lower risk profiles than human-modified forests. This underscores the need to protect primary forests, develop consistent large-scale data products to identify high-integrity forests, and operationalize a framework of ecosystem integrity. Doing so will optimize long-term carbon storage and the provision of other ecosystem services, and can help guide evolving forest policy at the nexus of the biodiversity and climate crises.